Gender Diversity And Firms’ Financial Performance In Malaysia - Yap, Irean Lee Kuen; Chan , Sok Gee; Zainudin, Rozaimah (Asian Academy of Management (AAM), 2017)
This study aims to investigate the relationship between gender diversity in a frm’s board of directors and fnancial performance of frms listed on Bursa Malaysia for the period between 2009 and 2013. Using unbalanced panel data analysis, we tested whether gender diversity in the boardroom may inﬂuence the frm’s performance, as measured by Tobin’s Q. We employed four different proxies for gender diversity (the dummy variable for women, the percentage of women on the board, the Blau index, and the Shannon index) to provide a more comprehensive measure of gender diversity. This study suggests that a higher degree of female representation on the board increases a frm’s fnancial performance. Positive discrimination favouring female boardroom appointment is therefore likely to persist as a feature of the corporate governance landscape in Malaysia.